Land use changes, natural regeneration patterns, and restoration practices after a large wildfire in NE Spain: Challenges for fire ecology and landscape restoration - Espelta, J. M.; Rodrigo, A.; Habrouk, A.; Meghelli, N.; Ordonez, J. L.; Retana, J. (FIRE AND BIOLOGICAL PROCESSES, 2002)
Great wildfires have recently affected sub-Mediterranean areas of central Catalonia (NE Spain). The large extension of the burned areas, as well as the fact that non-fire-prone vegetation has been severely affected, lead to ponder over the natural regeneration patterns occurring, and over the best strategies to restore and manage the burned areas. In the present study, we review the land use changes and the natural regeneration patterns observed after the large wildfire that occurred in Bages-Bergueda in 1994. The fire resulted in: (i) the creation of new croplands and pastures in previously forested areas, (ii) the expansion of mixed oak (Quercus ilex and Q. cerrioides) coppices, (iii) the failure of natural regeneration of the dominant tree species (Pinus nigra), leading to the appearance of areas without any tree regeneration. In this context, we discuss the results of different experiments carried out to reforest P nigra stands and to ameliorate the structure of mixed oak coppices.
The following values have no corresponding Zotero field: periodical: FIRE AND BIOLOGICAL PROCESSES pub-location: PO BOX 321, 2300 AH LEIDEN, NETHERLANDS
Keywords: land use changes; Mediterranean areas; natural regeneration; Spain; wildfires